Cenas de dissenso, arranjos disposicionais e experiências insurgentes : processos comunicativos e políticos em torno da resistência de estudantes secundaristas - Francine Altheman (2020)
The object of study of this thesis is the movements of insurgency, also known as the newest social movements, with the empirical process particularly focused on the secondary insurgency, that occupied over 200 schools in São Paulo in 2015. The objective of the research is to apprehend how communicative processes in these movements promote scenes of dissent and, consequently, change the involved individuals, in the sense of promoting their political emancipation. It is assumed that scenes of insurgency, and the events and performances that are unfolded at these scenes, allow shifts, rearrangements, and reconfiguration of types of legibility and intelligibility of the involved individuals’ lifestyle. The theoretical-analytical perspective, that guides the paths of this work, relies on the intertwining of Rancière’s perspective on the aesthetical and political dimensions of the scenes of dissent; the foucaultian dispositif and the constituent dispositional arrangements; and the Deleuzian experimentations. Other authors help to sew up the theoretical perspectives that underpin this research, and the main ones are Judith Butler, José Luiz Braga, Manuel Castells, Georges Didi-Huberman, Maurizio Lazzarato, Peter Pál Pelbart, among others. The methodological path was composed by three main axis: a) the proposal of allowing myself to be affected by the object before the theoretical-methodological development, as formulated by Jean-Luc Moriceau and Richard Soparnot; b) the method of equality, by Jacques Rancière, which involves the reconstruction of the scenes of dissent through narratives, documents and enunciative productions of the involved individuals; c) the foucaultian dispositif and the dispositional arrangements engaged in urgent situations, according to the rereading of José Luiz Braga. Therefore, the proposal presumes the reconstruction of the dissent scenes of the secondary students’ occupations, by analyzing their communicative processes, which involve the communication tactics of the newest social movements: the digital social networks’ appropriation, the performances on the streets, the occupation of public spaces, the body-camera, productions that involve gambiarra, the aesthetical experience and the articulation of insurgent bodies. Besides that, the analysis also explores the dispositional arrangements that produce the insurgent scenes, involving the confront with the police and the identity discussions about gender, social class, and race. The research, that was developed in a non-linear way, as a bricolage process, understands that the secondary students movement was one of the major insurgencies of the second decade of the 21st century and promoted their own communication tactics and methods, that engender the techniques of the self and the individuation processes. It is possible to say that the secondary students’ movement is a transforming revolutionary process, an uprising that still lives in artistic productions, in fabulative writings and in political actions by their main social actors: young people.